Pengembangan Alat Permainan Edukatif Boneka Tangan Untuk Menstimulasi Perkembangan Bahasa Anak Usia 4-6 Tahun Di Tk Dharma Wanita Persatuan Sarolangun - Tumewa Pangaribuan; Sarla Saffira; Siti Munifah; Nabila Vidri (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
This activity aims to stimulate the language development of children 4-6 at the Dharma Wanita Pertama Kindergarten Sarolangun using educational game tools. The research approach used is classroom action research, using data collection methods a) observation, b) conversation, and c) documentation. The results of the research stated that when the hand puppet stage activity was carried out, the children were very enthusiastic and the activity was carried out in a conducive manner where the children listened attentively and the children were given the opportunity to retell the story that had been told. This hand puppet stage performance provides feedback by asking questions and answers, children recognize various icons from the media used in telling stories (Kaaba, hand puppets, elephant troops, fire stones) as well as other supporting equipment, children have begun to understand so they can show good and bad behavior of the characters in the story